HYPOTHYROIDISM IN DOWN SYNDROME (DS) CHILDREN WITH CONGENITAL HEART DISEASE (CHD) - Zainuddin, Hanaa; Zahari, Norazah; Zaini, Azriyanti Anuar (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Down syndrome is the most common chromosomal disorder in liveborn infants, and is associated with thyroid dysfunction, estimated to occur in 4-8% of children. The reported incidence of congenital hypothyroidism (CHT) in children with Down syndrome is estimated 20 - 30 times higher than the incidence of CHT in the general population. We aim to investigate the prevalence of CHT in Down syndrome children with congenital heart disease (CHD) seen in our centre, as well as the aetiology of hypothyroidism in this group of paediatric patients. METHODOLOGY We performed a retrospective analysis of paediatric Down syndrome patients born between 1 January 1990 and 31 December 2020 who attended the paediatric cardiology clinic for routine review in the 3.25-year period between 1 September 2017 and 31 December 2020. RESULTS Children with DS accounted for 12.9% (n=62) of patients attending the paediatric cardiology clinic, with cyanotic CHD (cCHD) diagnosed in 29% (n=18) and acyanotic CHD (aCHD) in 71% (n=44). The prevalence of hypothyroidism in our population of DS children with all types of CHD was 19.4% (n=12). However, among DS children with cCHD, the prevalence of hypothyroidism was 22.2% (n=4/18), which was higher than the prevalence of hypothyroidism in aCHD, 18.2% (n=8/44). The mean age at presentation was 11.8 weeks (2 weeks – 32 weeks), and the mean TSH at presentation was 15.6 mIU/L (7.63 – 27.51 mIU/L). All patients with suspected CHT (n=12) underwent thyroid scintigraphy at age 3. Six patients (50%) were confirmed to have permanent CHT: 42% (n=5) had thyroid dyshormonogenesis, and 8% (n=1) had thyroid dysgenesis. None had ectopic thyroid. Autoimmune hypothyroidism occurred in 8% (n=1). Subclinical hypo-thyroidism occurred in 42% (n=5). CONCLUSION The prevalence of CHT in DS children with CHD is 50% in this studied population. Children with DS tend to present later with subclinical hypothyroidism rather than high cord TSH. Routine screening in the first year of life is mandatory to detect thyroid abnormalities.